الذمَّةُ الماليَّة للزَّوجَة العاملة: دراسةٌ تقويميَّة: (Financial Independence of Working Wives: An Evaluative Study) - زينب زكريا علي معابدة (At-Tajdid - Intellectual Refereed Journal, 2024)
Abstract This study in its theoritical part addresses the subject of the financial independence of a working wife in Islamic Sharia and Jordanian Personal Status Law, as well as issues related to ordering financial matters in the event of commingling of the spouses' fund. It also aims to illustrate the practical reality of the financial independence of working wives in Jordanian society through an empirical study that reveals this reality from social, intellectual, legal, and Sharia perspectives. The study employs inductive and descriptive methodologies, it concluded, in its theoritical part, that a working wife has an independent financial liability, in both Sharia and in the Jordanian Personal Status Law, and that marriage is not a reason for merging their financial liabilities. In its practical part, the study concluded that social and intellectual perspective indicates the existence of customs and traditions adopted by both men and women that encourage some overreach concerning the material rights of working wives. The study also highlights some shortcomings of Sharia scholars in clarifying the rulings related to the finances of working wives, and legal deficiencies that make the stipulation of financial independence for wives in the Jordanian Personal Status Law insufficient to protect their material rights. Therefore, it is necessary to legislate legal provisions concerning the participation of working wives in financial expenditures, since this issue has become a reality affecting family stability Keywords: Financial Disclosure, Financial Independence of Spouses, Financial Relationship between Spouses, Personal Status Law.